Rivalry for political change in Thailand - Tan, Seng Chye (2009)
The People's Alliance for Democracy (PAD) seems determined to confront the People Power Party (PPP) government and to pressure it to resign. The PAD seems to be seeking political change in Thailand from a democratically-elected parliament to an appointed one with partially-elected representatives. What will this all mean for Thailand?